PENGARUH MATHMAGIC DENGAN MODEL PEMBELAJARAN SCRAMBLE TERHADAP HASIL BELAJAR SISWA - Natalia Elisabet Marbun; Rohani Rohani; Rahma Muti'ah; Suriyani Suriyani (MES: Journal of Mathematics Education and Science, 2019)
Abstract. Learning outcomes are a measure of the success of students in learning the material delivered by the teacher. Data on students 'mathematics learning outcomes obtained at Bilah Hulu 2 High School showed that students' mathematics learning outcomes were relatively low so it was necessary to improve them, especially on mathematics subjects. The objectives of this research were to find out knowing the effect of mathmagic on the scramble learning model on student learning outcomes in the subject matter of Inverse Functions. This type of research is quantitative research using The One Group Pre-Post Test test Design. The research instruments used tests of student learning outcomes in the form of multiple choices. Data were analyzed by the T-Test, namely Paired Sample T-Test. The results average learning outcomes of class X MIA 1 Bilah Hulu 2 High School before being taught using mathmagic with a scramble learning model of 10.14 and a standard deviation of 3.563 and after being taught using mathmagic with scramble learning model of 16, 72 and standard deviation 2,987. Because the data obtained from the results of the t-test at a significance level of 0.05 is t count t table that is 16.784 2.045 then Ha is accepted. From these results, it can be concluded that there is a mathmagic influence with the scramble learning model on student learning outcomes by matching the question cards and answer cards available in random circumstances.Keywords: Mathmagic, Scramble, Learning Outcomes